2021
DOI: 10.1155/2021/8207283
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Supplementation with Filipendula ulmaria Extract Attenuates the Systemic Adverse Effects of Nanosized Calcium Phosphates in Rats

Abstract: The aim of this study was to investigate and compare the systemic toxicity of three nanosized calcium phosphates (CaPs): hydroxyapatite (HA), tricalcium phosphate (TCP), and amorphous calcium phosphate (ACP) in rats. Since those metallic compounds are widely used as bone replacement materials, including their use in oral surgery, CaPs were applied (per os) equimollary (17.8 mg/kg, 11 mg/kg, and 9.65 mg/kg b.w., respectively) for 30 days in order to mimic the previously described release rate from dental compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…ALT is distributed in the cytoplasm, and the increase of ALT indicates that the membrane is damaged. AST is distributed in cytoplasm and mitochondria, and elevation suggests that the damage has reached organelle level [ 31 , 32 ]. If the liver is damaged or damaged, transaminases in liver cells enter the bloodstream, and elevated levels of ALT and AST in the blood signal liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…ALT is distributed in the cytoplasm, and the increase of ALT indicates that the membrane is damaged. AST is distributed in cytoplasm and mitochondria, and elevation suggests that the damage has reached organelle level [ 31 , 32 ]. If the liver is damaged or damaged, transaminases in liver cells enter the bloodstream, and elevated levels of ALT and AST in the blood signal liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that the metallic compounds used as restorative materials can be also harmful by means of serious adverse effects [37,38]. Both metallic restorative compounds and nanoparticles may show numerous types of toxicities [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that the metallic compounds used as restorative materials can be also harmful by means of serious adverse effects [37,38]. Both metallic restorative compounds and nanoparticles may show numerous types of toxicities [37,38]. One of the main toxicity mechanisms is oxidative damage, and since curcumin (with confirmed antioxidant capacity [39], also in nanoformulation [40]), has been employed in this study, it appears reasonable to potentiate the beneficial role of curcumin in the prevention of those adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…5 Electrons leak from the electron transport chain directly to oxygen, producing short-lived free radicals such as superoxide anion. 5 Scepanovic et al 6 had been reported that antioxidant addition with extract of Filipendula ulmaria reduces the toxic effects of nano-sized calcium phosphates in rats. Oxidative stress, apoptotic, and inflammatory response are the main mechanisms of toxicity of La 2 O 3 NPs.…”
Section: Introductionmentioning
confidence: 99%